Analysing morphological errors in ESL graduating students’ writing based on sur-face structure taxonomy / Kamisah Ariffin … [et al.] - Ariffin, Kamisah; Darus, Norizul Azida; Abdul Halim, Norhajawati; Awang, Nurul Akmal (Universiti Teknologi MARA, 2021)
Empirical studies have examined errors committed by ESL learners at different levels of study in terms of its inconsistency with the standard form of English grammar rules in general. This study, on the other hand, looked into the errors in the English morphological system of a language that deals with the minimal units of linguistic form and meaning. By understanding the errors from the morphological perspective, instructors may also be able to figure out the specific causal factors that can help devise their methods and approach to teaching. As the English language performance of the graduates in this country has been publicly lamented by employers, this study focused on the writing products of graduating students to see the common errors made and to understand the interfering factors so that any intervention initiatives to improve their English language proficiency can be objectively proposed. The data were procured from a mock writing exit test of 60 graduating students from a public university. The Theory Taxonomy of Dulay or Surface Structure Taxonomy frame-work was used for data analysis. The data were treated quantitatively in terms of frequency counts of errors occurred in each category. The findings indicate that the errors were prevalent in the Omission category, followed by Addition, Misformation and Disordering. This has significant pedagogical implications on developing intervention or remedial programmers Empirical studies have examined errors committed by ESL learners at different levels of study in terms of its inconsistency with the standard form of English grammar rules in general. This study, on the other hand, looked into the errors in the English morphological system of a language that deals with the minimal units of linguistic form and meaning. By understanding the errors from the morphological perspective, instructors may also be able to figure out the specific causal factors that can help devise their methods and approach to teaching. As the English language performance of the graduates in this country has been publicly lamented by employers, this study focused on the writing products of graduating students to see the common errors made and to understand the interfering factors so that any intervention initiatives to improve their English language proficiency can be objectively proposed. The data were procured from a mock writing exit test of 60 graduating students from a public university. The Theory Taxonomy of Duly or Surface Structure Taxonomy frame-work was used for data analysis. The data were treated quantitatively in terms of frequency counts of errors occurred in each category. The findings indicate that the errors were prevalent in the Omission category, followed by Addition, Malformation and Disordering. This has significant pedagogical implications on developing intervention or remedial programs for graduating students. for graduating students.